A Model of Career Development for Student-Athletes - Coleman, Victoria D.; Barker, Shirl A. (My University, 1991)
This article outlined a comprehensive career development model for student-athletes that was being utilized at a major research university in the Midwest. It highlighted many internal (e.g., lack of previous work experience, fear of failure) and external barriers (e.g., few role models, societal expectations) athletes have when considering career development. The model consists of six components: (1) Introduction and Orientation; (2) Self-Assessment; (3) Decision Making; (4) Educational, Occupational, and Community Information; (5) Preparation for Work, Leisure, and Retirement; and (6) Research and Evaluation. Implications for personal, academic, and career counseling professionals and educational institutions were also discussed.
Keywords: career development